The massive double-lined O-type binary HD 165052 - Arias, Julia Ines (2002)
We present a new optical spectroscopic study of the O-type binary HD 165052 based on high- and intermediate-resolution CCD observations. We re-investigated the spectral classification of the binary components, obtaining spectral types of O6.5 V and O7.5 V for the primary and secondary, respectively, finding that both stars display weak C IIIλ5696 emission in their spectra. We also determined a radial-velocity orbit for HD 165052 with a period of 2.95510±0.00001 d, and semi-amplitudes of 94.8 and 104.7±0.5 km s-1, resulting in a mass ratio Q=0.9. From a comparison with previous radial-velocity determinations, we found evidence of apsidal motion in the system. Several signatures of wind–wind collision, such as phase-locked variability of the X-ray flux and the Struve–Sahade effect, are also considered. It was also found that the reddening in the region should be normal, in contrast with previous determinations.